Incongruencia jurídica entre el código orgánico de la producción, comercio e inversiones y la constitución de la república del ecuador, en la solución de conflictos por medio del arbitraje internacional. - Espinosa Quezada, Cesar Augusto (2015)
Being the Constitution of the Republic of Ecuador rule supreme over any other existing law within the Ecuadorian territory, where all the guidelines for both citizens, acting as the public sector in their administrative or judicial action are established. Set the public administration as a service to the entire collectivity which should also comply with some requirements both background and shape, in the action of its assistance to the community. Likewise, the production, trade and investment should be given in stages of production, distribution, Exchange, trade, consumption, handling of externalities and productive investments orientated in search of the good life; In addition, within the lower standards and what the present topic it relates within investment processes, generates difficulties, not respecting the constitutional legal framework and also belittling the constitutional principles by absence of proper coherence between standards of less hierarchy in regard to the settlement of disputes in international arbitration. The systematic lack of hierarchy in contractual investment processes, brings with it, that within the legal dispute between the State and natural or legal persons, there is a loophole or a contradiction at the time that the legislator drafted the law, there is no consistency with the constitutional norm. These errors are that the State will lose legal credibility, not having the confidence of a norm of less hierarchy, which contradicts the Constitution. It also produces losses to the Treasury by the loss of foreign investment since foreign capital will not enter Ecuadorian territory, for not having confidence in laws and also because not is providing them the necessary legal certainty due to incompatibility in the laws of less hierarchy, producing not only damage to the public sector; but, the beneficiaries of tax, production and streamlining of the economy in each place where it is made an investment to boost in the sector of Ecuadorian society. Situation that aroused my interest and will be centerpiece of the respective study; for the application of the alternative solutions.